Supply Chain Distribution Challenges and Solutions: A Case of an Indonesian Cement Manufacturing Company - Rifda Taqiyyah Taqiyyah; Siti Nursyamsiah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study explores the distribution system of a major cement manufacturing company in Indonesia within the context of its supply chain operations. Utilizing a qualitative descriptive approach, data were gathered through participatory observation and in-depth interviews conducted during a four-month internship in the company's logistics division. The findings reveal that the company operates a structured and technology-supported distribution network, employing ERP, GPS, and RFID systems while collaborating with third-party transporters. The distribution process involves order handling, delivery planning, loading, and monitoring. Despite this, several challenges remain, including equipment failures, limited real-time stock visibility, and disruptions due to weather and infrastructure limitations. The study provides actionable recommendations to improve operational efficiency and delivery accuracy, offering valuable insights for both logistics practitioners and academics interested in supply chain management in complex geographic environments.